Zinc oxide nanostructures for fluorescence and Raman signal enhancement: a review - Marica, Ioana; Nekvapil, Fran; Ștefan, Maria; Farcău, Cosmin; Falamaș, Alexandra (Beilstein Journal of Nanotechnology, 2022)
Since the initial discovery of surface-enhanced Raman scattering (SERS) and surface-enhanced fluorescence (SEF), these techniques have shown huge potential for applications in biomedicine, biotechnology, and optical sensors. Both methods rely on the high electromagnetic fields created at locations on the surface of plasmonic metal nanoparticles, depending on the geometry of the nanoparticles, their surface features, and the specific location of analyte molecules. Lately, ZnO-based nanostructures have been exploited especially as SERS substrates showing high enhancement factors and increased charge transfer effect. Additionally, applications focused on enhancing the fluorescence of analyte molecules as well as on tuning the photoluminescence properties of ZnO nanostructures through combination with metal nanoparticles. This review covers the major recent results of ZnO-based nanostructures used for fluorescence and Raman signal enhancement. The broad range of ZnO and ZnO–metal nanostructures synthesis methods are discussed, highlighting low-cost methods and the recyclability of ZnO-based nanosubstrates. Also, the SERS signal enhancement by ZnO-based nanostructures and the influences of lattice defects on the SERS signal are described. The photoluminescence enhancement of ZnO in the presence of noble metal nanoparticles and the molecular fluorescence enhancement in the presence of ZnO alone and in combination with metal nanoparticles are also reviewed.
Keywords: fluorescence; surface-enhanced Raman spectroscopy; ZnO–metal nanomaterials; ZnO nanostructures